Pertanggungjawaban Tindak Pidana terhadap Pembunuhan Berencana : (Studi Putusan No 174/Pid.B/2023/Pn.Sit) - Lailatur Rofiqoh; Yulius Efendi; Teguh Wicaksono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The criminal act committed by the perpetrator of premeditated murder is a very heinous act, because the perpetrator has the heart to kill people for certain reasons even though he is committing an act that is against the law. Legal accountability for perpetrators of the crime of premeditated murder is in accordance with article 340 of the criminal code, namely in the form of punishment, either the death penalty or imprisonment for a maximum period of twenty years or life. The problem in this research is the regulation of premeditated murder, the factors that cause premeditated murder and criminal liability for perpetrators in the crime of premeditated murder. The theories used in this research are the theory of responsibility and the theory of judge's consideration. The research method in this writing is a normative method that collects library data, namely statutory regulations, legal books, judge's decisions, and scientific journals related to the problems discussed in this thesis. The results of the research and discussion in this research are regarding the regulation of premeditated murder, which is stated in Article 340 of the Criminal Code, criminal responsibility for perpetrators in the crime of premeditated murder by paying attention to the elements of committing an unlawful act, the ability to be responsible, the element of error, If there is no justification or excuse, it is punishable by the threat of death or life imprisonment or a maximum of twenty years and the judge's consideration of premeditated murder is that it has been legally proven as in the indictment to violate Article 340 of the Criminal Code.